Development of Compartment Syndrome after Radial Artery Puncture in a Patient with Acute Hypoxemic Respiratory Failure due to COVID-19 - Orlando Garner; Krishidhar Nunna; Andrea Braun (Case Reports in Medicine)
A 71-year-old man who was recently hospitalized for COVID-19 pneumonia complicated by acute hypoxemic respiratory failure and severe ARDS requiring noninvasive ventilation was transferred to our hospital from a rehabilitation facility for new onset right wrist and hand pain and swelling which had been attributed to arterial thrombosis and empirically treated with therapeutic anticoagulation. He developed numbness and paralysis in his right hand and was diagnosed with right forearm compartment syndrome requiring emergent fasciotomy. After a prolonged hospital stay complicated by respiratory failure requiring mechanical ventilation, he was discharged with improved, but not resolved, sensorimotor deficits. Arterial blood gas sampling is commonly performed in patients with acute hypoxemic respiratory failure, for assessment of oxygenation and acid-base status. It is considered a benign procedure, but it can lead to serious complications, such as bleeding and compartment syndrome. Risks and benefits of any procedure need to be weighed carefully and less is often more. Compartment syndrome is characterized by the 5 P’s—pain, pallor, paresthesia, pulselessness, and paralysis.